Generation of hard transition X-rays by relativistic electrons in multilayered metal targets - Andreyashkin M. Yu.; Kaplin V. V. Valeriy Viktorovich; Uglov S. R. Sergey Romanovich; Zabaev V. N. Viktor Nikolaevich; Yoshida K.; Endo I. (1998, 1998)
Title screen